The determinants of capital structure of electrical and electronics companies in Malaysia / Nurul Ainin Syazwani Mohd Asri - Mohd Asri, Nurul Ainin Syazwani (2021)
Capital structure can be defined as a particular combination of equity and debt to finance their company's overall operations and growth. It is very important because the decision will impact the economic growth. This research objective is to analyse the capital structure of Electrical and Electronics companies in Malaysia. The factors affecting the level of debt which is capital structure are profitability, tangibility and liquidity. The collection of data for this research study has come from secondary data that was collected from the Statements of Profit or Loss and other Comprehensive Income and Statements of Financial Position which started from the year 2010 until year 2019 that consists of 11 companies. This study has used panel data. Pecking Order Theory and Trade-off Theory were the theories that have guided this research study. This study found that profitability and liquidity were a significant relationship with the capital structure however, the tangibility was found to be insignificant.